Pengaruh asal populasi dan pohon induk terhadap pertumbuhan bibit meranti tembaga (Shorea leprosula Miq.) sebagai materi untuk perbanyakan klonal - Mashudi; Setiadi, Dedi (Jurnal Penelitian Kehutanan Wallacea, 2017)
Vegetative propagation has an important role in production of high quality planting stocks.Through vegetative propagation, the genetic potential of a mother tree will totally be inherited to the off-springs.This study aimed to determine the effects of population sources and clones on growth variation of Shorea leprosulaMiqshoot cuttings. Randomized Complete Block Design (RCBD) was used as an experimental design; which consists of two factors, i.e population sources(Muara Wahau, Berau, Kenangan,Ketapangand Carita) and clones(40 clones). In this study clone was nested in the population. The results showed that the clones and population sourcesinfluenced the rooting percentage, height growth, number of root, length of root and number of leaves of S.leprosulashoot cuttings. Rooting percentage of clones ranged between 66.7 –100.0% (2 groups difference), height growth rangedbetween 2.60 –6.80 cm (6 groups difference), number of root rangedbetween 2.1 –5.7 (9 groups difference), length of root ranged between 4.3 –15.8 cm (8 groups difference) and number of leaves ranged between 1.17 –3.57 (5 groups difference).